Subdural hematoma with symptom of epileptic attacks after subarachnoidal anesthesia - a case report - Ivanov, Emilija; Karadjova, Dafina; Doneva, Ana; Nojkov, Jordan; Sivevski, Atanas (University of Nis, Faculty of Medicine, 2018)
The study describes a case of subdural hematoma developed after cesarean section in a 34- year-old patient with normal intra-operative course. During the first twelve hours after the operation, the patient had a headache considered as post-dural puncture headache (PDPH) and was treated in that direction. After the third operative day the headache was reduced, and on the fifth day the patient was discharged from the hospital in good condition. As soon as the patient was discharged, the headache appeared again with stronger and persisting intensity and at the end it was accom- panied by epileptic seizure. MR scan showed subdural hematoma in absorption. After conservative therapy, the condition was improved and the patient was without neurologic consequences. The differences between PDPH and other types of headache, as well as the potential etiopathogenesis of subdural hematoma in obstetric patient, are discussed in this study. We have come to the conclusion that after the long persisting headache, if we take into consideration this complication as a possibility, the early diagnosis and adequate treatment could lead to complete recovery.
Keywords: subdural hematoma; cesarean section; post-dural puncture headache; neuraxial block; subarachnoid anesthesia